2014
DOI: 10.1002/pchj.58
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptors in the ventral hippocampus are involved in extinction memory in rats

Abstract: Fear extinction decreases conditioned fear responses that normally occur when a conditioned stimulus (CS) is repeatedly presented in the absence of an aversive unconditioned stimulus (US), which is the behavioral basis of exposure therapy for posttraumatic stress disorder (PTSD). However, knowledge about the neurobiology of extinction is insufficient. The present study investigated changes in the protein expression of mineralocorticoid receptors (MRs) and glucocorticoid receptors (GRs) in the dorsal hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Semi-quantification of total GR by Western blotting and by immunohistochemical techniques showed that levels of this protein were not affected 60 min after training in CFC in any of the hippocampal subregions. Several studies have also reported that the optical density (OD) of the total GR protein does not change, either in vitro after incubation of U2OS and HEK 293 cell lines with the GR agonist dexamethasone (Wang et al, 2002;Lambert et al, 2013), nor in vivo after training animals in fear conditioning (Xing et al, 2014). However, increasing this interval would be likely to induce a decrease in GR concentration in certain subregions of the hippocampus, since GR is a transcription factor that negatively self-regulates in certain brain areas after binding its hormone ligand (Sapolsky et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Semi-quantification of total GR by Western blotting and by immunohistochemical techniques showed that levels of this protein were not affected 60 min after training in CFC in any of the hippocampal subregions. Several studies have also reported that the optical density (OD) of the total GR protein does not change, either in vitro after incubation of U2OS and HEK 293 cell lines with the GR agonist dexamethasone (Wang et al, 2002;Lambert et al, 2013), nor in vivo after training animals in fear conditioning (Xing et al, 2014). However, increasing this interval would be likely to induce a decrease in GR concentration in certain subregions of the hippocampus, since GR is a transcription factor that negatively self-regulates in certain brain areas after binding its hormone ligand (Sapolsky et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The MR antagonist spironolactone (spiro, 75 ng/μL) and GR antagonist mifepristone (mife, 20 ng/ μL) was dissolved in DMSO and diluted in saline for a final concentration of DMSO 5%. The doses were determined from published studies (Korte, Boer, Kloet, & Bohus, 1995;Moncada et al, 2011;Xing et al, 2014) and pilots experiments in our lab. The function-blocking anti-BDNF antibodies (Chemicon, Temecula, CA; AB1513P) were diluted to working concentration (0.5 μg/0.8 μL) with saline (Slipczuk et al, 2009).…”
Section: Drugsmentioning
confidence: 99%
“…Accordingly, these findings may underlie-at least to some extent-the blunted glucocorticoid responsiveness in these animals. Importantly, several studies have suggested that fear extinction may rely on forebrain MRs during periods of low circulating CORT levels at the time of extinction training (88,89). Moreover, the balance between MR and GR activation seems to be crucial for adequately processing aversive memories (90).…”
Section: Blunted Corticosterone Induces Fear Extinction Deficitsmentioning
confidence: 99%